Intangible Outcomes - Kurt Wilson (Journal of MultiDisciplinary Evaluation)
Human life – and therefore the scope of human goals – includes dimensions that are both visible and countable (e.g., money, weight, attendance or tested proficiency) as well the invisible and intangible (e.g., hope, trust, faith, love, joy, peace). Furthermore, the visible and tangible aspects of life are intrinsically connected to and dependent on the invisible and intangible aspects - much as the visible branches and fruit of a tree are connected to and dependent on an underlying and hidden root structure. While the importance of intangibles can be understood intuitively, it can also be illustrated: 73% of all chartable giving in the U.S. goes to organizations that are explicitly religious, and 118,280 nonprofit organizations are so strongly identified with the intangibles of hope, trust, faith, love, joy, peace that they included one of these words in their name. While the intangible realities of human life are explicitly relevant to a large proportion of organizations we seek to serve, it is essentially ignored by current evaluation practice: only 10 articles within the American Journal of Evaluation, New Directions in Evaluation and Journal of Multidisciplinary Evaluation included even minimal reference to the most common intangibles. New evaluation theory and methodology to address this gap will be needed, and cross-disciplinary exploration with psychology, philosophy and sociology should guide this development. In the meantime, useful questions about intangibles can be drawn from the AEA guiding principles and addressing these can provide a useful starting point for evaluators seeking to consider intangibles within their evaluations.